3x+6x/3x+9x

Simple and best practice solution for 3x+6x/3x+9x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+6x/3x+9x equation:


x in (-oo:+oo)

((6*x)/3)*x+3*x+9*x = 0

2*x^2+12*x = 0

DELTA = 12^2-(0*2*4)

DELTA = 144

DELTA > 0

x = (144^(1/2)-12)/(2*2) or x = (-144^(1/2)-12)/(2*2)

x = 0 or x = -6

x in { -6, 0 }

See similar equations:

| -29=x-22 | | -7x+2=44 | | -10r-6=2+9r | | s(t)=-16t^2+64t+480 | | -2a+4+3a=12-26 | | 13=36-lognbsp;x | | .8c-.1c=.9c | | 11x+6=116 | | x-7/12=5/9 | | 6.5(60-x)+2x=3.5(60) | | 4(9x-2y)= | | 6.5x+2(60-x)=3.5(60) | | y+89=114 | | 6z-24y=120 | | z-81.6=81.6 | | y(1-2y)(2+3y)= | | 15=35-2log(x+4) | | (6x^4-15x^3-17x^2-10x-14)/(3x^2+2) | | 4y+5=8y+7 | | f-250=368 | | 14n-11-13n-8=-9 | | 73-69=100-78 | | z-81.6=8.16 | | (2b+1)(3b+3)= | | x/3+2=-2 | | 6.5x+2x=3.5(60) | | 6.5x+2xy=3.5(60) | | (n+3)(3n+3)= | | x+1/5-1/3=2x-11/15 | | 1/7x=4/3 | | (4x-5)(4x+4)= | | 6.5x+2y=3.5(60) |

Equations solver categories